(untitled) (Journal of Asian Development Studies, 2023)
This qualitative study explores the socio-psychological problems experienced by individuals who underwent home quarantine during the COVID-19 pandemic. Utilizing purposive sampling, twenty-one in-depth interviews were conducted with participants who had been diagnosed with COVID-19 and isolated at home. Thematic analysis of the data revealed key challenges including social stigma, emotional distress, fear of deterioration, loneliness, and lack of social support. Participants also reported anxiety related to family health, financial instability, and the ambiguity of medical information. Social isolation intensified feelings of helplessness, while informal support networks emerged as a critical coping mechanism. The findings highlight the need for community-based mental health support and targeted interventions to mitigate the psychosocial burden on home-quarantined individuals. This study contributes to the understanding of lived experiences during health crises and underlines the importance of inclusive, psychologically-informed public health responses.